Challenges of in vitro modelling of liver fibrosis - Ros-Tarraga, Patricia; Villanueva-Badenas, Estela; Sanchez-Gonzalez, Estela; Gallego-Ferrer, Gloria; Donato, M. Teresa; Tolosa, Laia (Frontiers in Cell and Developmental Biology, 2025)
Liver fibrosis has been proposed as the most important predictive indicator affecting prognosis of patients with chronic liver disease. It is defined by an abnormal accumulation of extracellular matrix components that results from necrotic and inflammatory processes and eventually impairs organ function. With no approved therapy, comprehensive cellular models directly derived from patient’s cells are necessary to understand the mechanisms behind fibrosis and the response to anti-fibrotic therapies. Primary human cells, human hepatic cell lines and human stem cells-derived hepatic stellate-like cells have been widely used for studying fibrosis pathogenesis. In this paper, we depict the cellular crosstalk and the role of extracellular matrix during fibrosis pathogenesis and summarize different in vitro models from simple monolayers to multicellular 3D cultures used to gain deeper mechanistic understanding of the disease and the therapeutic response, discussing their major advantages and disadvantages for liver fibrosis modelling.